A Descriptive Review of Genre-Based Pedagogy Studies (Towards Genre Awareness in EFL Context of Indonesia) - Tri Rina Budiwati (Ahmad Dahlan Journal of English Studies, 2021)
This paper reviews 11 studies on genre-based pedagogy. The studies have indicated the vital contribution of genre knowledge in EFL context, especially in reading and writing class. Having compared and highlighted the 11 studies, this recent review reveals the great significance of genre knowledge and awareness for EFL teachers and students, namely, they can help students understand genre as created, dynamic and ideological structures, aware of generic structure of texts, then create various type of texts as discourse, develop the rhetorical understanding and participate in the genres, that they can maintain the critical genre awareness. Furthermore, teachers also are more aware that students can create meanings and need supports. The review, then, proposes some ways to improve students' genre awareness that could be applied in EFL classes. The ways are (1) students can be asked to analyze genre gradually to learn the techniques of rhetorical analysis of various genres;Â Â (2) students are asked to criticize and practice writing flexibly various genres based on certain rhetorical patterns, context, and purpose; and (3) in exposing genres, teachers could do the steps recommended, such as finding the purpose and features, language scaffolding, modeling, joint instruction of the text, individual construction of the text, peer review and revision, free discussion and doing the assignment.